Establishing Warehouse Receipts as Debt Guarantees in Indonesia’s Sharia Economic Law - Hastarini, Arvita; Ariesta Wibisono Anditya; Elza Qorina Pangestika (Mu’amalah: Jurnal Hukum Ekonomi Syariah, 2024)
This study addresses Indonesian farmers' challenges in accessing credit due to limited collateral options recognized by financial institutions. Farmers often struggle with capital access, as their agricultural products are not classified as eligible collateral under existing regulations. As a result, they cannot use their crops as collateral due to the absence of legal provisions. The research aims to answer two main questions: How can the position of Warehouse Receipts be recognized as a Debt Guarantee Right in Indonesian law? What is the execution power of Warehouse Receipt guarantees if the debtor defaults? This study analyzes the relevant laws and regulations using a normative juridical research method with a statutory approach. The findings reveal that Law No. 9/2006 (amended by Law No. 9/2011) established a legal framework for Warehouse Receipts, transforming them from proof of custody into evidence of property rights. This legal recognition enables Warehouse Receipts to be used as collateral, providing farmers an avenue to access credit. Furthermore, the study concludes that the execution of Warehouse Receipt guarantees is enforceable in cases of debtor default, offering enhanced legal certainty for creditors.